Gender gaps across countries and skills: Demand, supply and the industry structure - Claudia Olivetti; Barbara Petrongolo (Queen Mary University of London, School of Economics and Finance, 2014)
The comovement between gender gaps in hours and wages across countries and skills reveals the presence of net demand forces shaping gender differences in labor market outcomes. This paper links the rich pattern of variation in gender gaps to the process of structural transformation. Based on a stylized, multi-sector equilibrium model, we illustrate that the gender bias in labor demand can be decomposed into measurable within- and between-industry components. Using comparable micro data across countries, we find that international differences in the industry structure explain more than eighty percent of the overall variation in labor demand between the U.S. and all other countries in our sample, and roughly one third of the overall cross-country variation in wage and hours gaps.
Keywords: E24; J16; J31; 330; Gender gaps; Skills; Demand and supply; Industry structure